Design Space Exploration and Resource Management of Multi/Many-Core Systems - Singh, Amit Kumar; Ganguly, Amlan; Singh, Amit Kumar; Ganguly, Amlan (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The increasing demand of processing a higher number of applications and related data on computing platforms has resulted in reliance on multi-/many-core chips as they facilitate parallel processing. However, there is a desire for these platforms to be energy-efficient and reliable, and they need to perform secure computations for the interest of the whole community. This book provides perspectives on the aforementioned aspects from leading researchers in terms of state-of-the-art contributions and upcoming trends.
English
Keywords: Technology: general issues; embedded computer systems; cyber security; system-level design and design-space exploration; multi-objective optimization; system trade-offs; energy-efficient computing; run-time management; machine learning; concurrent workloads; multi-core systems; processing-in-memory; near-memory processing; resource management; code annotation; compiler optimizations; online heuristics; energy efficiency; 3D-stacked memories; non-volatile memories; peak-power management; many-core; directed acyclic task graphs; high performance computing; data centers; resource allocation; profit; energy consumption; reinforcement learning; server consolidation; RF; NoC; OFDMA; simulator; routing; reconfigurable; Hybrid Application Mapping (HAM); many-core systems; embedded systems; composability; design space exploration (DSE); Network-on-Chip (NoC); real-time guarantees; predictability; multi/many-core platforms; reliability; mixed-criticality